PERANCANGAN INTERIOR PUSAT PELAYANAN DAN TERAPI ANAK AUTISME DI KOTA DENPASAR - Ni Made Yulistiani; Ni Made Sri Wahyuni Trisna; Ngurah Gede Dwi Mahadipta (LPPM Institut Desain dan Bisnis Bali, 2020)
Autism spectrum disorder or autism is a disruption circumstance of undeveloped brains affecting patient’s abilities in communicating and social interacting with others. Autism resulted in patient’s misbehaviour and limited patient’s interest. In some cases, some children having difficulties in interacting or communicating; they have their own world and abandoned social environment; therefore, it is called autism spectrum disorder or autism. The fact that some parents have not realized the autism symptoms on their children as well as being late in putting them in particular treatments is due to less inclusive facilities in Bali, particularly in Denpasar City, such as therapies room and other related facilities. An inclusive facility for autism children patients, and designing a room in accordance with the theme and concept taken by Methamorphoo with the concept of the Harmonious Line Of Scandinavian. In this design, some therapy rooms are provided including behavioral therapy including occupational therapy and ABA, speech therapy, physiotherapy therapy, play therapy, swimming therapy, transition classes and self development classes, it is expected this design is able to meet the therapeutic needs for autism children. Keywords: Interior, Autism, Therapy, Design